Evaluating the use of a customized digital navigation program to optimize bowel preparation in pediatric colonsocopy - Dankner, Lauren; Quiros, Jose Antonio; Volpert, Diana; Atreja, Ashish (Frontiers in Pediatrics, 2023)
Adequate bowel preparation is essential for optimal colonoscopy diagnosis and/or intervention.However, suboptimal bowel preparation occurs in as many as 1 in 3 pediatric colonoscopies, leading to missed diagnoses, procedural complications, wasted resources, and increased costs. Objectives: We aimed to evaluate the effect of an automated Pediatric Colonoscopy Digital Navigation Program (PC-DNP) on the quality of colonoscopy preparation among pediatric patients. Methods: The PC-DNP sent patients timely weight-based bowel preparation instructions, video and text-based educational modules, logistical information, and appointment reminders prior to their scheduled diagnostic and/or therapeutic colonoscopies. Physician reported bowel preparation quality among patients/caregivers who were prescribed the PC-DNP were compared to bowel preparation quality of a historical sample of patients/caregivers who received standard care instructions. Results: We found that the PC-DNP group had significantly higher bowel preparation quality than the standard care group. Conclusions: These results demonstrated that automated DNPs may be easily implemented into the pediatric gastroenterologists' practice and may help streamline and improve bowel preparation in pediatric patients.